Հայերէնի փոխառութիւնները թրքերէնէն - Եղիայեան, Արմենակ (տպ. Atlas)
The study focuses on diverse sorts of lexical borrowings of the Armenian language (particularly Western Armenian) from Turkish. The author groups these borrowings into two categories: a) word borrowings, and b) grammatic-syntactic borrowings. Regarding the word borrowings, the author considers several different sorts of word borrowing, like verbs, nouns, adjectives and numbers; verbs borrowed from Turkish but Armenianised by adding an Armenian correlative affix; partly Turkish juxtaposed verbs, where one of the words is Turkish and the other Armenian. Last but not least the author notes that in expressing superlative adjectives, Armenian has copied the Turkish mode by repeating the word, yet changing a letter, for instance ship-shidag, where the original word shidag has changed one of its letters. As for the syntactic borrowings, the author groups them under a number of headings and discusses each, for example, agglutination, word-groups, utterance, idioms, degrees of qualitative comparison, articles, narrative verbs, numerals, prepositions and postpositions, popular proverbs and sayings, relative-antecedent and word order. The author notes that most of these borrowings have become an irreversible part of the Armenian language, and argues that borrowings are not willed and are being practiced via a very natural route. The author, however, stresses that these borrowings do not shake the pillars of Armenian grammar and further research is needed to complete such an avenue of research.
Keywords: Հայերէնի փոխառութիւններ; Թուրքերեն; Լեզուաբանութեան տեսութիւն